MENEROPONG DAMPAK REGULASI TATALAKSANA PENGAWASAN KEPABEANAN DAN CUKAI - Safari, Agung Tri (JURNAL PERSPEKTIF BEA DAN CUKAI, 2020)
ABSTRACT:Since the enactment of the Director-General of Customs and Excise Regulation Number P-53 / BC / 2010 concerning Procedures for Customs and Excise Controlling, a new chapter of customs and excise controlling has begun, as one of the implementations of the Ministry of Finance's Bureaucratic Reform related to improving systems and procedures at the Directorate General of Customs and Excise (DJBC). The purpose of this research is to find out and analyze the impact of regulation on Procedures for customs and excise controlling on the implementation of work in the controlling division. The research method used is a qualitative approach. The research conducted is classified as exploratory and descriptive research because the problem under study is a problem that has never been explored before, while the target of the research is limited. The results of the study are based on the perception of the resource persons in the regulation of Customs and Excise Control Procedures have had a high impact on systematic, synergic, and comprehensive and are based on their main tasks and functions. However, revision still needs to be made in order to develop and improve the management of the supervision so that it can have the desired impact. Research on the impact of the management of this supervision has never been done before even though it has been national coverage but the number of interviewees is still limited (184 people) so it needs further research.Keywords: procedures, controlling, customs, excise ABSTRAK:Sejak diberlakukannya Peraturan Direktur Jenderal Bea dan Cukai Nomor P-53/BC/2010 tentang Tatalaksana Pengawasan Kepabeanan dan Cukai, dimulailah babak baru pengawasan kepabeanan dan cukai, sebagai salah satu implementasi Reformasi Birokrasi Kemenkeu terkait penyempurnaan sistem dan prosedur pada Direktorat Jenderal Bea dan Cukai (DJBC). Tujuan penelitian ini adalah untuk mengetahui dan menganalisis dampak regulasi Tatalaksana Pengawasan Kepabeanan dan Cukai terhadap pelaksanaan pekerjaan di unit kerja pengawasan. Metode penelitian yang dipergunakan adalah dengan pendekatan kualitatif. Penelitian yang dilakukan tergolong penelitian eksplorasi dan deskriptif karena masalah yang diteliti adalah permasalahan yang belum pernah dijajaki sebelumnya, sedangkan sasaran penelitiannya terbatas. Hasil penelitian adalah berdasarkan persepsi narasumber regulasi Tatalaksana Pengawasan Kepabeanan dan Cukai telah memberikan dampak sistematis, sinergis dan komprehensif serta berdasarkan tugas pokok dan fungsinya yang tinggi. Namun demikian masih perlu perbaikan dalam rangka pengembangan dan penyempurnaan atas tatalaksana pengawasan tersebut agar dapat lebih memberikan dampak sesuai yang diharapkan. Penelitian atas dampak tatalaksana pengawasan ini belum pernah dilakukan sebelumnya walaupun sudah secara nasional namun jumlah narasumbernya masih terbatas (184 orang) sehingga perlu penelitian berikutnya.Kata Kunci: tatalaksana, pengawasan, kepabeanan, cukai